2020
DOI: 10.2478/msp-2020-0067
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and mechanism of aluminum silicate mesoporous materials by F108 template

Abstract: Aluminosilicate mesoporous materials were synthesized using F108 template (polyethylene glycol-polypropylene glycolpolyethylene glycol) at a concentration of 0.034 g/ml and the molar ratio of Al2O3 to SiO2 was 0.09. The products were then characterized using nitrogen adsorption/desorption tests, scanning electron microscopy (SEM), and X-ray diffraction (XRD). The effects of various crystallization temperatures as well as sodium hydroxide concentrations on the average diameter, pore volume, surface area, and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…Adsorption increased when the relative pressure reached 0.8, and a narrow H3 hysteresis loop emerged. The capillary condensation stage of Li 2 S–CoFeP–CN shifted to a higher relative pressure, indicating that the porosity of this sample is lower than that of the CoFeP–CN. , Furthermore, since condensation and evaporation occur at higher relative pressures for larger pores, this shift also indicates that only the largest pores remained after introducing the Li 2 S. The CoFeP–CN pore-size distribution, calculated using the Barret–Joyner–Halenda (BJH) model, confirms that the material is dominated by mesopores (inset of Figure S5). The average pore diameter of Li 2 S–CoFeP–CN is higher than that of the CoFeP–CN composite, and the mesopore volume in Li 2 S–CoFeP–CN is substantially smaller than that of CoFeP–CN, demonstrating that Li 2 S was effectively impregnated into the CoFeP–CN mesoporous channels.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Adsorption increased when the relative pressure reached 0.8, and a narrow H3 hysteresis loop emerged. The capillary condensation stage of Li 2 S–CoFeP–CN shifted to a higher relative pressure, indicating that the porosity of this sample is lower than that of the CoFeP–CN. , Furthermore, since condensation and evaporation occur at higher relative pressures for larger pores, this shift also indicates that only the largest pores remained after introducing the Li 2 S. The CoFeP–CN pore-size distribution, calculated using the Barret–Joyner–Halenda (BJH) model, confirms that the material is dominated by mesopores (inset of Figure S5). The average pore diameter of Li 2 S–CoFeP–CN is higher than that of the CoFeP–CN composite, and the mesopore volume in Li 2 S–CoFeP–CN is substantially smaller than that of CoFeP–CN, demonstrating that Li 2 S was effectively impregnated into the CoFeP–CN mesoporous channels.…”
Section: Resultsmentioning
confidence: 72%
“…The capillary condensation stage of Li 2 S−CoFeP−CN shifted to a higher relative pressure, indicating that the porosity of this sample is lower than that of the CoFeP−CN. 35,36 Furthermore, since condensation and evaporation occur at higher relative pressures for larger pores, 37 this shift also indicates that only the largest pores remained after introducing the Li 2 S. The CoFeP−CN poresize distribution, calculated using the Barret−Joyner−Halenda (BJH) model, confirms that the material is dominated by mesopores (inset of Figure S5). The average pore diameter of Figure S6 displays the high-resolution valence band X-ray photoelectron spectroscopy (XPS) spectra of g-C 3 N 4 , CoFeP− CN, and Li 2 S−CoFeP−CN samples.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
“…As shown in Table 3, composites prepared from abundantly available and low cost sources in Thailand (Na2SiO3 and 13) 88.5 --Aluminosilicate 3) 45-298 -4.68-27.50 Activated carbon from Magonia pubescens fruit bark 14) 220-441 31-51 8.0-12.6 Mesoporous alumina 15) 334 -3.39 Mesoporous silica (MCM-41) 16) 500-528 -3.53-3.80 Infrared spectroscopy analysis was carried out on the vinasse and the carbon-silica composites to study the functional groups and the results are shown in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
“…Typical synthesis methods of mesoporous materials include hydrothermal 3) , microwave 2) or polymerization 4) . ※ 3 Biodiversity and Environmental Management Division, International College, Khon Kaen University Khon Kaen, Thailand †Corresponding author: nyuvarat@kku.ac.th Composite materials are a combination of two materials with different physical and chemical properties or mechanical and thermal properties.…”
Section: Introductionmentioning
confidence: 99%
“…The hysteresis loop is a characteristic feature of the isothermal adsorption-desorption graph form by mesoporous material due to capillary condensation of nitrogen in the pores of the particles homogeneous particles. IUPAC distinguishes porous materials into three types, namely microporous (< 20 nm), mesoporous (20-500 nm) and macroporous (> 500 nm) (Ma et al, 2020).…”
Section: Bet Analysis (Physisorption/adsorptiondesorption Isothermal ...mentioning
confidence: 99%